SOME NEW RESULTS ON GENERALIZED BS-HOMEOMORPHISMS (International Journal of Food and Nutritional Sciences, 2022)
we introduce two classes of maps called BS-sgs-homeomorphisms and BS-gsg homeomorphisms and study their properties. These bitopological notions are generalized from the topological notions in bitopological spaces. These generalizations are substantiated with suitable examples and investigated with utmost care.